Therapeutic Alliance Moderates Psychopathy-Outcome Relation in Treatment of Substance-Abusing Offenders - Heintzsch, Ronja (International journal of offender therapy and comparative criminology, 2026)
The present study attempts to clarify the relationship between psychopathy, the therapeutic alliance, and success of offender treatment. In a German sample of n = 89 convicted men in addiction treatment, we examined whether early therapeutic alliance ratings moderated the relationship between psychopathy, as measured by the Psychopathy Checklist – Revised (PCL-R), and treatment success within the first 6 months. Results indicated that a moderation model is appropriate, as the association between total PCL-R and treatment success differed as a function of perceived therapeutic alliance. Specifically, high psychopathy impaired treatment success when the alliance was simultaneously poor. Conversely, a good alliance seemed to buffer the adverse effects of psychopathy. No differential associations were found for PCL-R Factor 1 and Factor 2, and the moderation model held for both client-rated as well as therapist-rated alliance. Implications for improving treatment programs for psychopathic patients are discussed.